Factors consistently associated with utilisation of essential maternal and child health services in Nigeria: analysis of the five Nigerian national household surveys (2003–2018). Issue 9 (17th September 2022) - Kawakatsu, Yoshito; Adolph, Christopher; Mosser, Jonathan F; Baffoe, Peter; Cheshi, Fatima; Aiga, Hirotsugu; Watkins, David; Sherr, Kenneth H
Abstract : Objective: This study aims to identify the individual and contextual factors consistently associated with utilisation of essential maternal and child health services in Nigeria across time and household geolocation. Design, setting and participants: Secondary data from five nationally representative household surveys conducted in Nigeria from 2003 to 2018 were used in this study. The study participants are women and children depending on essential maternal and child health (MCH) services. Outcome measures: The outcome measures were indicators of whether participants used each of the following essential MCH services: antenatal care, facility-based delivery, modern contraceptive use, childhood immunisations (BCG, diphtheria, tetanus, pertussis/Pentavalent and measles) and treatments of childhood illnesses (fever, cough and diarrhoea). Methods: We estimated generalised additive models with logit links and smoothing terms for households' geolocation and survey years. Results: Higher maternal education and households' wealth were significantly associated with utilisation of all types of essential MCH services (p<0.05). On the other hand, households with more children under 5 years of age and in poor communities were significantly less likely to use essential MCH services (p<0.05). Except for childhood immunisations, greater access to transport was positively associated with utilisation (p<0.05). Households with longer travel times to the most accessible health facility were less likely to use all types of essential MCH services (p<0.05), except modern contraceptive use and treatment of childhood fever and/or cough. Conclusion: This study adds to the evidence that maternal education and household wealth status are consistently associated with utilisation of essential MCH services across time and space. To increase utilisation of essential MCH services across different geolocations, interventions targeting poor communities and households with more children under 5 years of age should be appropriately designed. Moreover, additional interventions should prioritise to reduce inequities of essential MCH service utilisation between the wealth quantiles and between education status.